Ein Zweiter epigraphischer Beleg für den Skythen Saumakos (IosPE I2 353)? - Gavrilov, Alexander K. (Hyperboreus, 2017)
A small decree fragment IosPE I2 353 was compared by V. Latyschev with a big Decree of Chersonitans honouring Diophantus (IosPE I2 352) and established as a close parallel to it, both to events described and to the stone and lettering as such. At the end of line 2 the preserved text reads: Σκύθας καὶ ΣΑ.[.], the two last letters on the right edge being only partly visible. As there are no reasons to choose some appellative or a toponym to be reconstructed after καί, the author considers the possibility that the lost nomen was an ethnonym to be written along with the Scythians. As there were many names of Iranian tribes beginning with Σα-, one could think esp. about Σα(υ)ρ(ο)μάται, the ﬁrst half-vanished letter after ΣΑ at the end of the line 2 showing traces of the vertical hasta as in Ι, Ρ, Τ, Υ. The main argument against such a conjecture comes, however, from the close similarity of the fragment to the big Diophantus’ Decree, where the Scythians are seen along with Rheuxinals and Taurians, while Sarmatians are not present at all. On the other hand, in the passage describing the culmination of the historical events in the big Decree for Diophantus (IosPE I2  352, col. II, lines 34 f.) Scythians are referred to together with the name of their chieftain Σαύμακος. Personally he is the most representative counter-part of Diophantus in this description (the fact was in the author’s opinion demonstrated by a sort of spacing in the big Decree, col. II, lines 40–42). A combination of the ethnonym with a personal name in IosPE I2 353 may seem awkward, but the pair “tribe + leader” was in fact typical for the Greek façon de parler from Homer till late antiquity, last but not least in the narrative of Strabo about the same events (7, 4, 3): Σκύθας ἐπολέμει Σκίλουρόν τε... Thus the author proposes to reconstruct Σκύθας καὶˆ Σαύ[μακον] in lines 2 f. of IosPE I2 353. At the end of the discussion, he brieﬂy comments upon the relationship of both decrees and tries to shed some light as to the status and the role of Saumacus in the struggles of the epoch.